The Paradox of Self-Fertile Varieties in the Context of Self-Incompatible Genotypes in Olive - Alagna, F.; Caceres, M. E.; Pandolfi, S.; Collani, S.; Mousavi, S.; Mariotti, R.; Cultrera, N. G. M.; Baldoni, L.; Barcaccia, G. (Frontiers in Plant Science, 2019)
Olive, representing one of the most important fruit crops of the Mediterranean area, is characterized by a general low fruit yield, due to numerous constraints, including alternate bearing, low flower viability, male-sterility, inter- and self-incompatibility (SI). Early efforts to clarify the genetic control of SI in olive gave conflicting results and only recently, has the genetic control of SI been disclosed, revealing that olive possesses an unconventional homomorphic sporophytic diallelic system of SI, dissimilar from others described plants. This system, characterized by the presence of two SI groups, prevents self-fertilization and regulates inter-compatibility between cultivars, such that cultivars bearing the same incompatibility group are incompatible. Despite the presence of a functional SI, some varieties, in particular conditions, are able to set seeds following self-fertilization, a mechanism known as pseudo-self-compatibility (PSC), as widely reported in previous literature. Here, we summarise the results of previous works on SI in olive, particularly focusing on the occurrence of self-fertility, and offer a new perspective in view of the recent elucidation of the genetic architecture of the SI system in olive. Recent advances in research aimed at unraveling the molecular bases of SI and its breakdown in olive are also presented. The clarification of these mechanisms may have a huge impact on orchard management and will provide fundamental information for the future of olive breeding programs.